Recent Advances in Silk Sericin/Calcium Phosphate Biomaterials - Veiga, Anabela; Castro, Filipa; Rocha, Fernando; Oliveira, Ana L. (Frontiers in Materials, 2020)
Calcium phosphates (CaPs) have been widely used in the field of biomedical engineering as bone graft substitutes or as carriers for drug delivery applications. Recent developments have focused on combining CaPs with proteins to obtain functional biomaterials that accommodate a broader spectrum of functional requirements. Silk sericin was considered an unutilized protein by-product from the textile industry, generating tons of residues every year. However, much effort has been dedicated to its recovery after being associated with numerous biological properties such as antioxidant, antibacterial, anti-coagulation and regenerative activities. In the past years, sericin has also demonstrated to be suitable as a template for CaP mineralization. The present review focuses on the recent developments for the production of sericin/CaP composites, exploring their potential applications in bioengineering and opening new avenues in other research fields such as in the cosmetic, food and environmental sectors. In addition, this paper can also be useful as a guideline to design future research based on sericin/CaP biomaterials.